The Sacred and the Myth: Havel’s Greengrocer, Twenty Years Later - Shore, Marci (East European politics and societies, 2018)
This essay juxtaposes two thinkers: the French literary critic and philosopher René Girard (1923?2015) and the Czech playwright, essayist, and dissident Václav Havel (1936?2011). In particular, the text examines Havel?s 1978 essay The Power of the Powerless through the lens of Girard?s structuralist model of mimetic desire, violent sacrifice, and a cultural order sustained by prohibition, ritual, and myth. Arguing against the French structural anthropologist Claude Lévi-Strauss (1908?2009), Girard insisted on a reality behind the text: myths disclosed real victims. Girard and Havel shared a merciless anti-populism: society was guilty. They shared something else as well: in an age of a loss of faith in Marxism and all grand narratives, and of skepticism about the possibility of any stable meaning, subjectivity, and truth, Havel and Girard insisted on the ontological reality of both truth and lies, and on the ontological reality of the distinction between them.